The Influence of Company Size, Profitability, and Audit Opinion on Audit Delay in Food and Beverage Subsector Manufacturing Companies Listed on the IDX in 2020-2023 - Utung, Maria Wilhelmina; Pradnyani, Ni Luh Putu Sri Purnama; Artaningrum, Rai Gina (Pertapsi-Indonesia collaborated with Petra Christian University, 2025)
Audit delay is the amount of time it takes for an auditor to finish their work. This time is counted from the end of the financial year to when the audit report is made public. The auditor shows their responsibility and job by sending in the audit report on time. When auditors follow the rules, it affects how long it takes to share their findings and how good those findings are. This study aimed to find out how company size, profit, and audit opinions affect how long audits take. It used numbers and information from other sources for the research. This study looked at 45 food and drink manufacturing companies listed on the IDX from 2020 to 2023. The method used to select samples was purposive sampling, which followed specific criteria to get 92 samples. The researchers used a method called multiple linear regression analysis to look at the data. The study found that larger companies tended to have longer audit delays. Making a profit caused audits to take longer. The audit opinion caused problems because it took too long to complete the audit. The results show that three things affect how long audits take: the size of the company, how much money it makes, and the auditor's opinion. The factors mentioned can help company leaders when growing the business and can guide investors when deciding where to put their money.